Aging in Asia: Trends, Impacts and Responses - Jayant Menon; Anna Melendez-Nakamura (Asian Development Bank (ADB), 2009)
By the middle of this century, Asia's elderly population is projected to reach 922.7 million, and its share of population 17.5%, from just 4.1% in 1950. Within the next few decades, Asia is poised to become the oldest region in the world; reforming policies and creating new structures and institutions to address this challenge is a huge and complex undertaking that requires a big head-start. This paper analyzes the impact that aging is having in Asia, examines the policy options for dealing with the problems it is causing, and outlines how different sub-regions may require different responses.
hdl:11540/1794
Keywords: J11; J14; J18; 330; Aging Asia; Asian demographic transition; Asian population trends; Asian population forecasts; aging impact